Ceratozetes (Ceratozetes) conjunctus Mihelcic 1956 - Murvanidze, Maka; Cilbircioğlu, Cihan; Özdemir, Esengül; Inak, Emre (Zenodo, 2020)
Ceratozetes (Ceratozetes) conjunctus Mihelčič, 1956 * Material – New record for Turkey. One specimen in Alasökü Village, Taşköprü forest, N 41° 19′ 55.68′′, E 34° 25′ 16.18′′, alt. = 1369 m, 16 June 2018; one specimen in Alasökü Village, Taşköprü forest, N 41° 19′ 55.16′′, E 34° 25′ 08.12′′, alt. = 1408 m, 2 July 2018; one specimen in Çamkonak forests, Daday, Kastamonu, N 41° 23′ 43.63′′, E 33° 13′ 38.96′′, alt. = 1215 m, 19 October 2018, tree trunk of P. sylvestris. Global distribution – Palaearctic. Ecology – Alpine meadow and forest soils.

Published as part of Murvanidze, Maka, Cilbircioğlu, Cihan, Özdemir, Esengül & Inak, Emre, 2020, Checklist of oribatid mites (Acari: Oribatida) of the Central Black Sea basin of Turkey with new records for the country, pp. 255-277 in Persian Journal of Acarology 9 (3) on pages 267-268, DOI: 10.22073/pja.v9i3.61909, http://zenodo.org/record/5236444
Keywords: Arthropoda; Arachnida; Ceratozetidae; Animalia; Ceratozetes conjunctus; Biodiversity; Sarcoptiformes; Ceratozetes; Taxonomy; 15. Life on land